One-Pot Synthesis of Aminated Bimodal Mesoporous Silica Nanoparticles as Antibacterial Nanocarrier and CO2 Capture Sorbent - Yun Li; Amit Kumar Tiwari; Jingyi Sandy Ng; Geok Leng Seah; Hong Kit Lim; Teeraporn Suteewong; Chor Yong Tay; Yeng Ming Lam; Kwan W. Tan (My University, 2022)
Mesoporous silica nanoparticles have highly versatile structural properties that are suitable for a plethora of applications including catalysis, separation and nanotherapeutics. We report a one-pot synthesis strategy that generates bimodal mesoporous silica nanoparticles via co-assembly of a structure-directing Gemini surfactant (C16-3-16) with tetraethoxysilane/(3-aminopropyl)triethoxysilane-derived sol additive. Synthesis temperature enables control of the nanoparticle shape, structure and mesopore architecture. Variations of the aminosilane/alkylsilane molar ratio further enables programmable adjustments of hollow to dense nanoparticle morphologies, bimodal pore sizes and surface chemistry. The resultant Gemini-directed aminated mesoporous silica nanoparticles have excellent carbon dioxide adsorption capacities and antimicrobial properties against E. coli. Our results provide enhanced understandings in the structure formation of multiscale mesoporous inorganic materials that are desirable for numerous applications such as carbon sequestration, water remediation and biomedical-related applications.
Keywords: Nanocarriers; Triethoxysilane; Mesoporous organosilica; Mesoporous Materials and Catalysis